IDENTIFIKASI MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA TAHUN 2000 - 2011 - Herlina, Deswita (KINERJA, 2013)
The aim of this research is to identify the working mechanism of various channels particularly interestrates, credits (bank lending and balance sheet), assets channels, exchange rates, on period 2000:1-2011:4.This research use time series secondary data take from BI, BPS and IFS from many publications. Analysistechnique that used was properties of Granger Causality.The results of Granger causality test showed that the SBI had a one-way relationship with PUAB and DEP,while PUAB has no relationship to KIBK and IRSS variables have one-way relationship with KIBK. Grangercausality test results on the interest rate channels of all the variables have one-way relationship, except KRSSvariable has no relationship with DEP. Granger causality test results on asset price channel is no relationshipbetween IRSS and KRSS against IHSG . The results are in exchange rate channel two-way relationshipbetween PSB with NFA, and NTRMUA have two-way relationship with the CPI and NTRMUA have no causalrelationship with the PDBR.Keywords: Monetary transmission mechanism, interest rates channels, credits channels, exchange rateschannels, Granger Causality